2017
DOI: 10.1002/slct.201701284
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Titanium Content in MWCNT@Sn1‐xTixO2 Composites on the Lithium Ion Storage Process

Abstract: We report the synthesis of multiwall carbon nanotubes@metal oxide composites (MWCNT@Sn 1-x Ti x O 2 ) and explore the lithium storage capacity and mechanisms in a broad range of compositions. The composite structures were synthesized by hydrothermal method using SnCl 4 and TiCl 4 as Sn and Ti sources, respectively. Oxide adherence on the carbon surface, as well as an optimum ratio between surface area and porosity, seem to be promoted by Sn content, with MWCNT@Sn 0.75 Ti 0.25 O 2 showing the best performance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…22 Therefore, using a ternary metal oxide such as Sn x Ti 1−x O 2 (where 0 ≤ x ≤ 1) that offers the ability to tune the E CBM as a function of composition is one strategy that can be used to control IET in WS-DSPECs. Sn x Ti 1−x O 2 solid solutions have been studied as photoanode materials in conventional dye-sensitized solar cells (DSSCs), 23−25 batteries, 26,27 and for photocatalysis. 28,29 In addition, there have been several experimental 30,31 and theoretical 32 studies on the properties of Sn x Ti 1−x O 2 solid solutions.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Therefore, using a ternary metal oxide such as Sn x Ti 1−x O 2 (where 0 ≤ x ≤ 1) that offers the ability to tune the E CBM as a function of composition is one strategy that can be used to control IET in WS-DSPECs. Sn x Ti 1−x O 2 solid solutions have been studied as photoanode materials in conventional dye-sensitized solar cells (DSSCs), 23−25 batteries, 26,27 and for photocatalysis. 28,29 In addition, there have been several experimental 30,31 and theoretical 32 studies on the properties of Sn x Ti 1−x O 2 solid solutions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Sn x Ti 1– x O 2 solid solutions have been studied as photoanode materials in conventional dye-sensitized solar cells (DSSCs), batteries, , and for photocatalysis. , In addition, there have been several experimental , and theoretical studies on the properties of Sn x Ti 1– x O 2 solid solutions. Notably in the context of DSSCs, Zhang et al suggested that Ti 4+ atoms incorporated into SnO 2 act as trap states that inhibit electron transport within the material, but increase the recombination lifetime .…”
Section: Introductionmentioning
confidence: 99%